(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
Arterial hypertension, a significant risk factor for cardiovascular illnesses, has posed intricate management issues, especially in patients following COVID-19. Recent evidence indicates that COVID-19’s effects on cardiovascular health may modify traditional hypertension therapy protocols. Recent studies reveal that post-COVID-19 patients frequently experience increased cardiovascular strain, which may be mitigated with non-pharmacological therapies. Investigating non-pharmacological strategies, such as lifestyle alterations encompassing physical activity, nutrition, and stress reduction, may offer alternative means to maintain blood pressure without dependence on medication. This retrospective study evaluates the effectiveness of these ways in managing arterial hypertension in post-COVID-19 patients, with the objective of identifying feasible strategies for preserving cardiovascular health and comprehending the wider implications of COVID-19 on hypertensive disorders.